Brassica juncea BRC1-1 induced by SD negatively regulates flowering by directly interacting with BjuFT and BjuFUL promoter - Feng, Junjie; Deng, Qinlin; Lu, Huanhuan; Wei, Dayong; Wang, Zhimin; Tang, Qinglin (Frontiers in Plant Science, 2022)
Flowering is crucial for plant reproductive success in angiosperms, and the core regulation factors such as FT, FUL and SOC1 are essential to accelerate flowering. BRANCHED1 (BRC1), a TCP transcription factor, plays an important role in regulating branches and flowering. However, the mechanisms of BjuBRC1 in regulating B. juncea flowering are largely unknown. Here, we reported four homologous genes of BjuBRC1 and provided an evidence that BjuBRC1 repressed flowering time. Subcellular localization and sequence analysis indicated that BjuBRC1 was located in nucleus with a TCP domain. Expression analysis revealed that BjuBRC1 was expressed abundantly in leaves, flowers and flower buds, and could be induced by short-day conditions in B. juncea. Overexpressing BjuBRC1 in Arabidopsis showed that BjuBRC1 could delay flowering time. Bimolecular fluorescent complimenEDDtary and luciferase complementation assays proved that BjuBRC1 could interact with BjuFT in vivo. Notably, BjuBRC1s could form heterodimers in vivo that probably impacted the function of negatively regulating flowering time. Yeast one-hybrid, dual-luciferase reporter assay and luciferase activity assay showed that BjuBRC1 could bind to the promoter of BjuFUL to repress its expression. Taken together, these results indicated that BjuBRC1 had a conserved function in negatively regulating flowering by cooperating with BjuFT and repressing the expression of BjuFUL.